Evaluation of a concept to classify anamnesis-related risk of complications and oral diseases in patients attending the clinical course in dental education - Gerhard Schmalz; Lena Brauer; Rainer Haak; Dirk Ziebolz (BMC, 2023)
Abstract Background Aim of the current study was the assessment of risk classes according to a previously established system to classify the anamnesis-related risk of complications and of oral diseases in a cohort of patients attending the dental student course for dental preventive measures. Methods Patients attending the student course between April 2020 and December 2021 were included. To assess the medical history, a specific anamnesis tool was used, which included the classification of different potential anamneis-related risks originating from general diseases, medications or lifestyle factors into a low, moderate or high risk of complications and/or risk of oral diseases. Thereby, the risk of complications was defined as the increaeed probability of harm during dental measures (professional tooth cleaning, invasive dental treatment or any kind of manipulation, which may cause a bacteremia), e.g. infectious endocarditis. On the other hand, the risk of oral diseases was an increaeed probability of development and/or progression of oral diseases like caries, periodontitis or mucosal diseases. Those risk classes were subsequently analyzed under consideration of age and gender. Results 858 patients, with a mean age of 50.48 ± 20.72 [median: 52.0] years, and a nearly balanced gender distribution (50.8% female and 49.2% male) were included. In the overall cohort, the risk of complications related with dental measures was low in 38.3%, moderate in 42.4% and high in 19.3% of participants. The risk of oral diseases was low in 33.1%, moderate in 37.2% and high in 29.7% of participants. Both, the risk of complications and the risk of oral diseases increased with patients' age (p < 0.01). Thereby, the risk of complications as well as the risk of oral diseases related to general diseases and medication significantly increased with age (p < 0.01). Conclusion Nearly one fifth of patients in dental student couse show a high risk of complications related with dental measures. Morever, nearly one third of those individuals have a high anamnesis-related risk of oral diseases. With increasing age, the amount of patients in high risk classes becomes higher. Future dental education and research should address the high relevance of anamnesis-related risk factors.